Widespread pesticide contamination of drinking water and impact on cancer risk in Brazil. (July 2022) - Panis, Carolina; Candiotto, Luciano Zanetti Pessôa; Gaboardi, Shaiane Carla; Gurzenda, Susie; Cruz, Jurandir; Castro, Marcia; Lemos, Bernardo
Graphical abstract: Abstract: Pesticides, which are associated with endocrine dysfunction, immunological dysregulation, and cancer, are widespread sources of drinking water contamination. The state of Paraná has a population of 11 million, is the second largest grain producer in Brazil and is a leading consumer of pesticides. In this study, we analyzed the extent of drinking water contamination from 11 proven, probable, or potentially carcinogenic pesticides (alachlor, aldrin-dieldrin, atrazine, chlordane, DDT-DDD-DDE, diuron, glyphosate-AMPA, lindane-γ-HCH, mancozeb-ETU, molinate, and trifluralin) in 127 grain-producing municipalities in the state of Paraná. Extensive contamination of drinking water was found, including legacy pesticides such as aldrin-dieldrin (mean 0.047 ppb), DDT-DDD-DDE (mean: 0.07), chlordane (mean: 0.181), and lindane-HCH (mean: 2.17). Most of the municipalities were significantly above the maximum limits for each one of the currently allowed pesticides (67% for alachlor, 9.44% for atrazine, 96.85% for diuron, 100% for glyphosate-AMPA, 80.31% for mancozeb-ETU, 91.33% for molinate, and 12.6% for trifluralin). Ninety-seven percent of municipalities presented a sum of all pesticides at levels significantly above (189.84 ppb) the European Union preconized limits (<0.5 ppb). Using the mean pesticide concentration in water (ppb), the exposed population for each municipality, and the benchmark cancer risk for pesticides, we estimated the minimum number of cancer cases attributable to pesticide-contaminated drinking water during the period (total of 542 cases). More than 80% were attributed to mancozeb-ETU and diuron. Glyphosate-AMPA and diuron-attributable cases strongly correlated with the total cancer cases in the same period (R = 0.8117 and 0.8138, respectively) as well as with breast cancer cases (R = 0.7695 and 0.7551, respectively). Water contamination was significantly correlated with the sum of the estimated cancer cases for all 11 pesticides detected in each city (R = 0.58 and p < 0.0001). These findings reveal extensive contamination of drinking water in the state of Paraná and suggest that contamination may increase the risk of cancer in this region.